OnabotulinumtoxinA detrusor injection improves female sexual function in women with overactive bladder wet syndrome. (June 2018) - Balzarro, Matteo; Rubilotta, Emanuele; Braga, Andrea; Bassi, Silvia; Processali, Tania; Artibani, Walter; Serati, Maurizio
Abstract: Objectives: The correlation between changes in sexual function and improvements in LUTD in patients treated with OnabotulinumtoxinA (onaBoNT-A) detrusor injection is unclear and limited only to women with neurogenic OAB. The aim of this study was to evaluate the impact of OnabotulinumtoxinA (onaBoNT-A) injection on sexual function in women undergoing this treatment for idiopathic wet overactive bladder (OAB). Study design: This is a pilot three-center observational study including women affected by idiopathic wet overactive bladder refractory to standard conservative treatments and underwent onaBoNT-A injection. Sexuality was assessed using the Female Sexual Function Index (FSFI). A 3-day voiding diary, OAB screener questionnaire (OAB-S), and the international consultation on incontinence questionnaire short form (ICIQ-sf) were completed before and 3 months after onaBoNT-A injection to evaluate OAB symptoms. Results: All the 32 enrolled patients were included for statistical analysis. These patients received 100U of onaBoNT-A. Significant improvement of many FSFI domains was found. Only desire and pain domains had no significant improvements. The FSFI total score showed a significant improvement (P 0.0008). Clinical efficacy has been documented by voiding diaries, OAB-S scores, and ICIQ-sf scores. Correlation between UUI episodes and FSFI total score was statistically significant ( r = −0.73; p = 0.04) while no significant correlation was found between the number of micturition and FSFI total score. Conclusion: Women who underwent successful OnaBoNT-A detrusor injection to treat wet OAB, showed an improvement in sexual function due to the significant correlation between the improvement of urinary urge incontinence and a better gratification of sexuality.